Antihyperglycemic effects of Lysiphyllum strychnifolium leaf extract in vitro and in vivo - Arman Syah Goli; Vilasinee Hirunpanich Sato; Hitoshi Sato; Savita Chewchinda; Jiraporn Leanpolchareanchai; Jannarin Nontakham; Jantana Yahuafai; Thavaree Thilavech; Pongsatorn Meesawatsom; Metawee Maitree (Taylor & Francis Group, 2023)
AbstractContext Lysiphyllum strychnifolium (Craib) A. Schmitz (LS) (Fabaceae) has traditionally been used to treat diabetes mellitus.Objective This study demonstrates the antidiabetic and antioxidant effects of aqueous extract of LS leaves in vivo and in vitro.Materials and methods The effects of aqueous LS leaf extract on glucose uptake, sodium-dependent glucose cotransporter 1 (SGLT1) and glucose transporter 2 (GLUT2) mRNA expression in Caco-2 cells, α-glucosidase, and lipid peroxidation were evaluated in vitro. The antidiabetic effects were evaluated using an oral glucose tolerance test (OGTT) and a 28-day consecutive administration to streptozotocin (STZ)-nicotinamide (NA)-induced type 2 diabetic mice.Results The extract significantly inhibited glucose uptake (IC50: 236.2 ± 36.05 µg/mL) and downregulated SGLT1 and GLUT2 mRNA expression by approximately 90% in Caco-2 cells. Furthermore, it non-competitively inhibited α-glucosidase in a concentration-dependent manner with the IC50 and Ki of 6.52 ± 0.42 and 1.32 µg/mL, respectively. The extract at 1000 mg/kg significantly reduced fasting blood glucose levels in both the OGTT and 28-day consecutive administration models as compared with untreated STZ-NA-induced diabetic mice (p < 0.05). Significant improvements of serum insulin, homeostasis model assessment of insulin resistance (HOMA-IR), and GLUT4 levels were observed. Furthermore, the extract markedly decreased oxidative stress markers by 37-53% reduction of superoxide dismutase 1 (SOD1) in muscle and malondialdehyde (MDA) in muscle and pancreas, which correlated with the reduction of MDA production in vitro (IC50: 24.80 ± 7.24 µg/mL).Conclusion The LS extract has potent antihyperglycemic activity to be used as alternative medicine to treat diabetes mellitus.